Children hospitalized due to maltreatment in the ICU of a Public Health Service - Letícia Medeiros Santomé; Sandra Maria Cezar Leal; Joel Rolim Mancia; Antônio Marcos Freire Gomes
ABSRACT Objective: to characterize children hospitalized due to violence in a pediatric ICU in 2011; to relate violence and the mechanisms of trauma with death; to know the contextualization of violence, from the records in the medical records. Method: retrospective cohort, performed in a first aid hospital, Porto Alegre city, in the records of 22 children hospitalized in the ICU due to violence. Quantitative analysis was performed by absolute and relative frequency rates, chi-square and relative risk. Results: 54.5% were boys, 81.8% were white and 50% were up to three years old. Physical violence 50% and neglect 36.4%, family of children (77.3%), highlighting the mother (35.3%). Mechanisms of aggression: fall (22.7%), burns (18.2%). Burns were at high risk for death. Discharge to go home after ICU admission (59.1%). Conclusion: It is considered that the characterization of the cases of violence reflects the complexity of the theme, mainly, in face of the life histories that surround each case of children hospitalized by this aggravation.